Heparin length in the coating of extremely small iron oxide nanoparticles regulates in vivo theranostic applications. Issue 2 (22nd December 2020) - Groult, Hugo; Carregal-Romero, Susana; Castejón, David; Azkargorta, Mikel; Miguel-Coello, Ana-Beatriz; Pulagam, Krishna Reddy; Gómez-Vallejo, Vanessa; Cousin, Rémi; Muñoz-Caffarel, María; Lawrie, Charles H.; Llop, Jordi; Piot, Jean-Marie; et al.
Abstract : The length of heparin oligosaccharides in the coating of extremely small iron oxide nanoparticles can control core size during synthesis for optimal positive MRI contrast, endow probes with specific bioactivities and majorly impact the in vivo pharmacokinetic properties. Abstract : The positive contrast of extremely small iron oxide nanoparticles (ESIONP) in magnetic resonance imaging (MRI) rejuvenates this class of metal nanoparticles (NP).Yet, the current synthesis often lacks the possibility of adjusting the core size (while it is a key element for ESIONP-based MRI contrast behaviour), and also involved multiple complex steps before obtaining a ready-to-use probe for medical applications. In this study, we faced these challenges by applying heparin oligosaccharides (HO) of different lengths as coatings for the preparation of HEP-ESIONP with a one-pot microwave method. We demonstrated that the HO length could control the core size during the synthesis to achieve optimal positive MRI contrast, and that HEP-ESIONP were endowed directly with anticoagulant properties and/or a specific antitumor activity, according to the HO used. Relevantly, positron emission tomography (PET)-based in vivo biodistribution study conducted with 68 Ga core-doped HEP-ESIONP analogues revealed significant changes in the probe behaviours, the shortening of HO promoting a shift from hepatic to renal clearance. The different conformations of HO coatings and a thorough in vitro characterisation of the probes' protein coronas provided insight into this crucial impact of HO length on opsonization-mediated immune response and elimination. Overall, we were able to identify a precise HO length to get an ESIONP probe showing prolonged vascular lifetime and moderate accumulation in a tumor xenograft, balanced with a low uptake by non-specific organs and favourable urinary clearance. This probe met all prerequisites for advanced theranostic medical applications with a dual MRI/PET hot spot capability and potential antitumor activity.